Gondolatok a természetvédelem és társadalom kapcsolatáról a Duna–Dráva Nemzeti Park létesítése kapcsán - Lájer, Konrád (Tér és Társadalom, 1995)
The Danube–Dráva National Park, close to the time of its implementation, is a special complex of flood land gallery forests spotted with mortlakes, of marshlands, fenwoods, sandy Iowlands, beech-, hornbeam- and Austrian oak-forests. This means a system of habitats which, significantly expanding and connecting the already protected areas, improves the chances of survival for the populations of the species that live there, ensuring this way the ecological services for the society for a long run. During history this region provided a good living for the people who líved here, while at the same time a traditional economy compatible with the ecological conditions was created, with the complex use of the resources (fishing, animal husbandry, forestry, meadow cultivation, fruit growing). During the annual floods the dams and canals gradually spread water in the whole of the flood land: In the fishing lakes, meadows, the bottom of the orchards and the pastures. In the time of recession water was releaed back to the river-bed, and at the culverts between the dams all the fish were caught this time. This special flood land economy was sustainable for a long while until external disturbances (destruction of wars, river canalisations, expansion of goods production) forced its frameworks apad. For nature protection it is favourable that in the major part of the region the density of population is below the national average. The growth of tourism and the priority of the traditional, labour intensive forms of economy will create jobs for the population. From the aspect of agriculture, the penetration of bio-economy means a new chance. The meadows with trees that have special landscape value can be sustained by grazing, the marshlands by mowing, offering a precious use for traditional animal husbandry. The possibilities of the revitalisation of the flood land economy to a certain levei are given, also for the support of traditional animal (e.g. grey cattle) and fruit species. Approximately 63% of the territory of the national park is covered by forests in the majority of which forestry will continue in the future. In the article a proposition was stated so that the real values of the different kinds of services offered by the forests should really appear in the economic processes: From a money fund separated for this purpose those engaged in forestry would obtain differentiated annual grants after the natural value (defined by objective methods) of the forest that they maintain. In case of a negative natural value the owner would pay this fee to the fund. As a results of the measures of nature protection, the ability of the territories to maintain game will increase, favouring game economy. Resulting from the endowments of the region, fishing and angling will keep their importance, but this latter one has to be harmonised with the requirements of nature protection, because it is not sustainable in its present form. By the establishment of exhibition spots, tourist paths and the familiarisation of the values of the national park, the possibilities of tourism will increase. Eco-tourism is given a special attention, since it aims at the discovery and study of special natural values. The National Park, by offering personal experiences, promotes the formation of a new perception and knowledge of nature protection in the growing generations. The varied, beautiful and clean environment is an inappreciable value for the development of the children. The protection of the natural values and drinking water bases makes the so far neglected sewerage system and sewage purification in the villages an urgent task. River canalisation, changing the water system can only take place in favour of nature protection. The water supply, the holding back of the water will bring some economic benefits for the water-dependent living habitats, as well.